2013
DOI: 10.1530/eje-12-0993
|View full text |Cite
|
Sign up to set email alerts
|

Low malignancy risk of thyroid follicular lesion of undetermined significance in patients from post-endemic areas

Abstract: Objective: New classification of the thyroid fine-needle aspiration biopsy (FNAB) results tries to stratify the risk of malignancy of thyroid follicular lesions using 'follicular lesion of undetermined significance' (FLUS) subcategory. Clinical significance of this category in the endemic (or post-endemic) areas has not been clearly established. Design: The aim of the study was to determine the risk of malignancy for FLUS as well as to evaluate ultrasound (US) malignancy risk features (MRF) in such nodules in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…In our previous study we reported that FLUS nodules showed US features of intermediate values between BL and SFN nodules [16]. In the present study the frequency of particular UMRFs in ISC nodules was evaluated in relation to the final histopathological examination.…”
Section: Prace Oryginalnementioning
confidence: 83%
See 1 more Smart Citation
“…In our previous study we reported that FLUS nodules showed US features of intermediate values between BL and SFN nodules [16]. In the present study the frequency of particular UMRFs in ISC nodules was evaluated in relation to the final histopathological examination.…”
Section: Prace Oryginalnementioning
confidence: 83%
“…Smears were fixed in 95% ethanol solution and stained with haematoxylin and eosin. A detailed description of the FNA procedure was presented in our earlier work [16][17].…”
Section: Prace Oryginalnementioning
confidence: 99%
“…Tumours infiltrating the thyroid by direct extension from neighbouring organs and lymphomas were included in the analysis. The details on FNA protocol and cytological outcome classification at our department were reported previously [20]. Surgical thyroidectomy specimens were processed by standard procedures.…”
Section: Methodsmentioning
confidence: 99%
“…This category is supposed to be an indication for control FNAB in order to clarify the diagnosis [3,4]. Our previous analyses demonstrated that FLUS mainly allows the extraction from the group of follicular lesions ones that are associated with a lower risk of cancer [5]. However, the definition of FLUS is wider.…”
Section: Introductionmentioning
confidence: 99%
“…Smears were fixed in 95% ethanol solution and stained with hematoxylin and eosin. A detailed description of the FNAB procedure was presented in our earlier work [5].…”
mentioning
confidence: 99%